At a crossroads: Genetic lineages and dispersal routes of Morimus asper (Sulzer, 1776) s.l. (Coleoptera, Cerambycidae) in Bulgaria - Rumyana Kostova; Simeon Borissov; Aneliya Bobeva; Rostislav Bekchiev (Biodiversity Data Journal, 2024)
The present study fills a knowledge gap in the distribution and genetic variation of Morimus populations in the Balkans, by studiyng the representatives of the genus in Bulgaria – M. asper funereus Mulsant, 1862, M. verecundus bulgaricus Danilevsky, 2016 and M. orientalis Reitter, 1894. Additional information is provided for Albania and northern Greece. The mitochondrial cytochrome C oxidase subunit I (COI) marker and the nuclear internal transcribed spacer 2 (ITS2) were used for the genetic analyses. Three of the previously-defined mitochondrial lineages (Lb/HgA, L2 and L3) were detected in Bulgaria, as well as a new lineage (Str) from the Strandzha Mountains (south-eastern Bulgaria). A total of 24 distinct haplotypes, 20 of them in Bulgaria, were found. Bulgarian populations of Morimus demonstrated relatively high nucleotide diversity. The L3 COI lineage was confirmed as the most diverse and frequent in the Balkans. The L3 lineage is dominant in most of Bulgaria, but was not identified in the easternmost parts near the Black Sea coast, where the L2 and Str lineages were found. New data highlighted two dispersal routes of the L2 mitochondrial lineage on the Balkan Peninsula: 1) northwards along the Black Sea coast and 2) westwards, across the Balkans where only disjunct populations remain. North-western Bulgaria seems to be the eastern limit of the basal lineage Lb/HgA distribution. Our results show high levels of genetic exchange between most of the mitochondrially defined lineages, yet some of the easternmost populations probably remained isolated for comparatively longer periods.